Study of Pancasila as the Foundation of the Economic Education Curriculum in Indonesia - Agussalim, Agussalim; Wahyuni, Wahyuni; Yani, Ahmad; Suaeb, Suaeb (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Pancasila as the nation's philosophy must be used as the main foundation of education in Indonesia. Economic education does not only transfer economic knowledge, but must also transfer Pancasila values as economic actors who are not only rational but also have high social sensitivity and concern. This research aims to examine the concept and implementation of Pancasila as a foundation for economic education in Indonesia. This research is classified as descriptive research regarding expert opinions referred to in several references (textbooks and journal articles) published online. The results of the study show that Pancasila is the basis for formulating and implementing the education curriculum in Indonesia, especially in the independent learning curriculum which emphasizes the Pancasila Student Profile. So far, Pancasila values are still partially taught as specific subjects so they have not been comprehensively integrated into educational and economic learning materials. The results of a review of various relevant research results show that economic education material in Indonesia is dominated by the philosophical foundation of neoclassical-capitalist materialism which is not relevant to national ideology